2019
DOI: 10.3390/su11247175
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Willingness for Centralized Biogas Production in Hebei and Shandong Provinces

Abstract: Nowadays, in the North China Plain (NCP), most counties and suburban rural regions are promoting the "coal to gas" program under the situation of strong government support of large and medium-sized centralized biogas production (CBP) projects. This paper is aimed at the CBP projects, focuses on rural residents’ “willingness to use (WTU)”, “willingness to buy (WTB)” and the influencing factors for WTU/WTB. Through the analysis of rural residents from Hebei and Shandong provinces that belong to NCP in this surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…First, in order to ensure production capacity, it is necessary to fully understand the market demand of the product. Wang et al (2019), according to a survey, found the willingness to buy for CBP products is $10.1 per capita, and analyzed the factors affecting residents' willingness to buy [57]. It is also necessary to adapt the needs of farmers to the local conditions and respect farmers' living habits, improve the accessibility and affordability [58].…”
Section: Discussionmentioning
confidence: 99%
“…First, in order to ensure production capacity, it is necessary to fully understand the market demand of the product. Wang et al (2019), according to a survey, found the willingness to buy for CBP products is $10.1 per capita, and analyzed the factors affecting residents' willingness to buy [57]. It is also necessary to adapt the needs of farmers to the local conditions and respect farmers' living habits, improve the accessibility and affordability [58].…”
Section: Discussionmentioning
confidence: 99%
“…The new percentage of the proposed construction subsidy will cover 25% to 40% of the total investment. On one hand, the subsidy system should be based on demand response, whilst a reasonable subsidy rate is the premise of the effectiveness of the financial support policy [53]. Approximately 0.9 CNY/Nm 3 biogas is discussed as output subsidy.…”
Section: Reconsidering Governmental Subsidy In Chinamentioning
confidence: 99%
“…Knowledge, Attitude and Practice (KAP) are three evidence-based structures used to understand professionals' behavior and behavioral changes in oral care [21,22]. KAP regarding oral hygiene refers to knowledge as the "understanding of the topic regarding oral hygiene", attitude as "feelings towards oral hygiene, as well as predetermined ideas towards oral hygiene", and practice as "ways to demonstrate knowledge and attitudes through behavior towards oral hygiene [23,24]. Albrecht et al [25] conducted a systematic review to assess the effects of oral hygiene educational interventions for nursing staff or residents on the maintenance or improvement of the oral health of nursing home residents, which involved educational sessions on oral hygiene for nursing staff (five trials) or for both staff and residents (four trials).…”
Section: Introductionmentioning
confidence: 99%